THE LAW GLOBALIZATION IN CYBERCRIME PREVENTION - Siregar, Gomgom TP; Sinaga, Sarman (International Journal of Law Reconstruction, 2021)
Globalization makes the world without borders, countries compete freely in various fields, and sometimes cross the jurisdictional limits of a country, overcoming cybercrime in legislation is absolutely necessary. Related to the jurisdiction of this crime which is a global crime, it is necessary to have a separate law that regulates cybercrime. The approach method using normative juridical. The results of research and discussion stated that The law globalization and politics provides cybercrime countermeasures in the application of legal norms between nations, which increasingly play an important role, especially how to regulate all forms of advances in information technology, communication, and transportation. This is inseparable from the foreign policy that has been woven between nations so far. Cybercrime regulation in legislation is absolutely necessary. Regarding jurisdiction over this crime, which is a global crime, it is necessary to have a separate law that regulates cybercrime, namely cyber law, which also regulates its jurisdiction by including the principle that allows cybercrime actors who harm the state even though they are outside the territory of the country.